Recent glacier decline in the Kerguelen Islands (49°S, 69°E) derived from modeling, field observations, and satellite data - Verfaillie, D.; Favier, V.; Dumont, M.; Jomelli, V.; Gilbert, A.; Brunstein, D.; Gallée, H.; Rinterknecht, V.; Menegoz, M.; Frenot, Y. (Journal of Geophysical Research: Earth Surface, 2015)
Date of Acceptance: 28/02/2015 The retreat of glaciers in the Kerguelen Islands (49°S, 69°E) and their associated climatic causes have been analyzed using field data and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite images to validate a positive degree-day (PDD) model forced by data from local meteorological stations. Mass balance measurements made during recent field campaigns on the largest glacier of the Cook Ice Cap were compared to data from the early 1970s, providing a 40 year view of the differences in the spatial distribution of surface mass balance (SMB). To obtain additional regional data for the validation of our models, we analyzed MODIS images (2000-2012) to determine if our model was capable of reproducing variations in the transient snow line. The PDD model correctly simulated the variations in the snow line, the spatial variations in the SMB, and its trend with elevation. Yet current SMB values diverge from their classic linear representation with elevation, and stake data at high altitudes now display more negative SMB values than expected. By analyzing MODIS albedo, we observed that these values are caused by the disappearance of snow and associated feedback on melt rates. In addition, certain parts of Ampere Glacier could not be reproduced by the surface energy balance model because of overaccumulation due to wind deposition. Finally, the MODIS data, field data, and our models suggest that the acceleration of glacier wastage in Kerguelen is due to reduced net accumulation and an associated rise in the snow line since the 1970s. Peer reviewed